FISHERY, GROWTH, YIELD PER RECRUIT AND STOCK ASSESSMENT OF SPHYRAENA OBTUSATA CUVIER OFF TUTICORIN, GULF OF MANNAR - Kasim, H Mohamed; Balasubramanian, T S (Indian Journal of Fisheries, 2026)
Annual average catch of 612.2 t of barracudas were landed at the catch rate of 17.1 kg/unit which constituted3.9% in the total catch landed by trawlers during 1987 - ’89 at Tuticorin. Higher effort input duringcertain months did not coincide with better abundance of barracudas. Sphyraena obtusata Cuvierconstituted on an average 69.6% of the total catch of barracudas. Based on the length-frequency data,the growth ^ameters have been estimated to be L <Â»> 470.0 mm, K 1.0364/year and t^ -0.0098 ye. Thenatural mortality coefficient (M) is 1.591, the average annual total mortality coefficient (Z) is 2.8317 andthe average exploitation rate (U) is 0.4123. The average standing stock is estimated to be 343.2 t andaverage annual stock 1,032.71. Yield per recruit studies indicate that S. obtusata is not exposed to higherfishing pressure as the average fishing mortality coefficient (F), 1.2407, for the prevailing age at firstcapture, 0.4709 ye is lower than the respective F,^which can yield the Y,^ in both the M/K ratios 1.0and 1.535. There is scope for increasing the effort of trawl net with a view to increase the catch of thisspecies at the prevailing conditions.